Integrative genetic and multi-omics analysis reveals the interleukin-6 receptor’s role in recurrent spontaneous abortion - Ma, Weixu; Gu, Zhongjia; Lin, Qiwang; Cao, Mingzhu; Zhong, Junmin; Li, Xin; Li, Hongyan; Lin, Yue; Lin, Han; Xu, Mengchang; Liu, Jianqiao; Du, Lili; et al. (Frontiers in Immunology, 2025)
BackgroundRecurrent spontaneous abortion (RSA) significantly impacts women’s health, yet the underlying biological mechanisms remain poorly defined. Understanding the molecular contributors to RSA is crucial for developing targeted interventions.ObjectiveThis study aims to investigate the causal relationships between plasma proteins and RSA, focusing on the identification of potential therapeutic targets through multi-omic approaches.MethodsWe utilized two-sample Mendelian randomization (MR) analyses integrating genome-wide association study (GWAS) data for both plasma proteins and RSA. Proteomic data were sourced from the UK Biobank-Plasma Proteome Project and deCODE Health Study. We further validated our findings through both bulk and single-cell RNA sequencing of clinical specimens, alongside quantitative real-time polymerase chain reaction and immunohistochemistry. A phenome-wide association study was also conducted to assess the safety and broader implications of identified targets.ResultsOur analyses identified the interleukin 6 receptor (IL6R) as a key candidate, with elevated plasma levels correlating with increased RSA risk. Furthermore, IL6R was found to be upregulated in RSA-related endometrial and decidual tissues. The phenome-wide association study provided insights into potential side effects and additional therapeutic indications for IL6R.ConclusionIL6R upregulation is mechanistically implicated in the pathogenesis of RSA, establishing it as a validated causal biomarker and a potentially actionable therapeutic target. This study not only highlights the role of IL6R in RSA but also supports its development into a therapeutic strategy with a comprehensive safety profile.